The emerging roles of exosomes in autoimmune diseases, with special emphasis on microRNAs in exosomes. (July 2021) - Miao, Chenggui; Wang, Xiao; Zhou, Wanwan; Huang, Jinling
Abstract: Autoimmune diseases include rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic vasculitis, dermatomyositis, systemic sclerosis (SSc), mixed connective tissue disease, autoimmune hemolytic anemia, autoimmune thyroiditis (AITD) and ulcerative colitis. Exosomes exist in body fluids, including blood, saliva, urine, cerebrospinal fluid and milk. They are mainly derived from the invagination of intracellular lysosomal particles, which are released into the extracellular matrix after fusion of the outer membrane of the exosomes with the cell membrane. Exosomes mediate intercellular communication and regulate the biological activity of receptor cells by carrying proteins, nucleic acids and lipids. Evidences show that exosomes are involved in the pathogenesis of various autoimmune diseases. In view of the important roles of exosomes in autoimmune diseases, this work systematically reviewed the effects of exosomes on the pathogenesis of autoimmune diseases, especially the regulatory roles of exosome derived microRNAs (miRNAs) in the pathogenesis of RA, SLE, dermatomyositis, SSc, AITD and ulcerative colitis. The review of the roles of exosomes in autoimmune diseases will help to clarify the pathogenesis of these diseases and explore new diagnostic markers and therapeutic targets. Graphical Abstract: ga1 Highlights: Exosomes mediate intercellular communication and regulate biological activity. Exosomes are involved in the pathogenesis of various autoimmune diseases. This work systematically reviews the roles of exosomes in autoimmune diseases. Exosomes derived miRNAs mediate the roles of exosomes.